2008
DOI: 10.1080/09540100802243325
|View full text |Cite
|
Sign up to set email alerts
|

Antibody binding to hazelnut (Corylus avellana) proteins: the effects of extraction procedure and hazelnut source

Abstract: The quality of an applied protein extract is important in both serological and in vivo diagnosis of allergy, and for allergen detection methods. In the present study the effects of the extraction procedure and hazelnut source on antibody binding to hazelnut (Corylus avellana) proteins were investigated. An overnight extraction procedure in trisÁ glycine buffer at 458C was compared to a quick, vigorous extraction in a tris buffer at room temperature (RT). Antibody binding was studied by the use of polyclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…A similar phenomenon was reported for almond Pru du 1 . In contrast, nsLTPs and seed storage proteins in hazelnut and almond appeared very stable . Studies examining the effect of thermal processing on the allergenicity of cashew nut, Brazil nut, pecan nut, walnut and pistachio were scarce and limited in their scope.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A similar phenomenon was reported for almond Pru du 1 . In contrast, nsLTPs and seed storage proteins in hazelnut and almond appeared very stable . Studies examining the effect of thermal processing on the allergenicity of cashew nut, Brazil nut, pecan nut, walnut and pistachio were scarce and limited in their scope.…”
Section: Discussionsupporting
confidence: 69%
“…IgE binding to roasted and unroasted hazelnut was comparable in two different studies: two patients with severe hazelnut allergy [180°C, 15 min, by ELISA (enzyme‐linked immunosorbent assay)] and five patients sensitized to Cor a 9 (±170°C, 10 min, using ELISA and immunoblot). Intact Cor a 9 was detected in roasted hazelnut paste . Another study showed that Cor a 9 and Cor a 11 and an allergen <14 kD (Cor a 14) were stable after roasting at 185°C for 15 min .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, even after being submitted to high temperatures, the secondary structures of these proteins remain unchanged or with minor modifications, suggesting that the characteristic beta-barrel motif is highly stable. Preliminary studies on raw hazelnuts submitted to dry heat treatment at 170ºC, indicated that the protein profile and the amount of Cor a 9 was not affected until after 20 min of roasting (Dooper et al, 2008). More recently, López et al (2012) verified that Cor a 9 is a highly well-structured protein, enriched by a beta-sheet core and with long unstructured loops.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…So far, only a few papers were reported on the evaluation of food processing effects on hazelnut proteins, and most of them focused on the fate of allergenic proteins upon thermal treatment. In particular, Cor a 1, Cor a 2, and Cor a 8 were proved to be thermolabile proteins [40][41][42], whereas Cor a 9 and Cor a 11 allergens were considered more thermostable [43][44][45]. In addition, Cor a 9 and Cor a 11, under particular processing condition, could generate Maillard reactions and advanced glycation end products [44,45].…”
Section: Varietal Diversity Andmentioning
confidence: 99%